Extraction Efficiency of Different Solvents and LC-UV Determination of Biogenic Amines in Tea Leaves and Infusions - U. Gianfranco Spizzirri; Nevio Picci; Donatella Restuccia (Journal of Analytical Methods in Chemistry)
Biogenic amines (BAs), that is, spermine, spermidine, putrescine, histamine, tyramine, β-phenylethylamine, cadaverine, and serotonin, have been determined in several samples of tea leaves, tea infusions, and tea drinks by LC-UV method after derivatization with dansyl chloride. Different extraction solvents have been tested and TCA 5% showed better analytical performances in terms of linearity, recovery percentages, LOD, LOQ, and repeatability than HCl 0.1 M and HClO4 0.1 M and was finally exploited for the quantitative determination of BAs in all samples. In tea leaves total BAs concentration ranged from 2.23 μg g−1 to 11.24 μg g−1 and PUT (1.05–2.25 μg g−1) and SPD (1.01–1.95 μg g−1) were always present, while SER (nd–1.56 μg g−1), HIS (nd–2.44 μg g−1), and SPM (nd–1.64 μg g−1) were detected more rarely. CAD and PHE were determined in few samples at much lower concentrations while none of the samples contained TYR. Tea infusions showed the same trend with total BAs concentrations never exceeding 80.7 μg L−1. Black teas showed higher amounts of BAs than green teas and organic and decaffeinated samples always contained much lower BAs levels than their conventional counterparts.